Therapeutic Hypothermia as Effective Therapy For ROSC Patients With Cardiac Arrest: A Systematic Review - Kurniawati, Fidiana; Astarani, Kili (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This systematic review aimed to identify therapeutic hypothermia as a safe and effective action in post cardiac arrest patients and the appropriate time and temperature for the procedure. This research was taken from the electronic database PubMed, Science Direct, EBSCO, and Google Shcolar, through database scanning, and article screening was carried out independently by researchers. Researchers followed the requirements in fulfilling the inclusion criteria. We used all electronic search strategies for each electronic database according to inclusion data, with search strings: therapeutic hypothermia, prehospital, out-of-hospital Cardiac Arrest, randomized controlled trials. Therapeutic hypothermia is safe and effective for use in ROSC patients with cardiac arrest and the right time to perform this action is at the pre-hospital time with the use of a temperature of 34-36 ° C